Pengaruh Dimensi Customer Experience Terhadap Satisfaction Dan Customer Loyalty (Studi Pada Cokelat Klasik Cafe Malang) - Sugysti, Ririn (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this study to analyze and explain the relation between the influence of customer experience dimension and the customer satisfaction and loyalty of customers of Cokelat Klasik Cafe Malang. The data of this explanatory research. Using non-probability sampling method with purposive sampling technique, 200 samples. From visitors ofÂ  Cokelat Klasik Cafe Malang who had visited Cokelat Klasik Cafe Malang more than 2 times were selected. The data were analyzed using SmartPLS ver. 3.0 through the stage of outer model, inner model, and hypothesis testing. The results show that customer experience dimension consisting of physical environment, interaction with staff, and interaction with other consumers have a significant effect on customer satisfaction. The results of this study show that there is a significant and positive influence satisfaction on the loyalty of costumers of Cokelat Klasik Cafe Malang. Keywords: customer experience dimension, satisfaction, customer loyalty